2021
DOI: 10.1039/d1nr05729d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surface chemistry on the interfacial evaporation-driven self-assembly of thermoplasmonic gold nanoparticles

Abstract: This work reports an interfacial evaporation-driven approach for self-assembly of a thermoplasmonic gold nanoparticle film at the interface of liquid/air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Here, the use of light presents several advantages over the use of magnetic fields such as site-specific delivery and wavelength-dependence. Due to these reasons, light-driven chemistries such as cis–trans isomerization, , use of photoacids, , photochemical cycloadditions, and photothermal effects , have been extensively exploited to design reversible self-assembly of NPs. In this direction, Grzybowski and co-workers used light-induced dipole–dipole and covalent interactions for the assembly of colloidal crystals and supraspheres (Figure c and vide infra).…”
Section: Different Ways To Make Self-assembled Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the use of light presents several advantages over the use of magnetic fields such as site-specific delivery and wavelength-dependence. Due to these reasons, light-driven chemistries such as cis–trans isomerization, , use of photoacids, , photochemical cycloadditions, and photothermal effects , have been extensively exploited to design reversible self-assembly of NPs. In this direction, Grzybowski and co-workers used light-induced dipole–dipole and covalent interactions for the assembly of colloidal crystals and supraspheres (Figure c and vide infra).…”
Section: Different Ways To Make Self-assembled Structuresmentioning
confidence: 99%
“…In another set of examples, the thermoplasmonic properties of metal NPs have been utilized to trigger the self-assembly process at the nanoscale. , The heat dissipated from a photoexcited NP will create a thermal gradient resulting in the preferential movement of particles (thermophoresis), thereby initiating the self-assembly. In this direction, Zheng and co-workers have used plasmon-mediated thermophoresis to demonstrate a reversible self-assembly of Au nanotriangles with excellent control over the aggregate size and morphology (Figure d) .…”
Section: Different Ways To Make Self-assembled Structuresmentioning
confidence: 99%
“…Upon light irradiation, plasmonic AuNPs eventually dissipate the excess energy in the form of heat to the surroundings within a few picoseconds via a series of nonradiative relaxation steps (Landau damping, electron–electron, electron–phonon, and phonon–phonon interactions, Figure b). ,, The thermal energy dissipated is often termed as plasmonic heat and forms the basis for the area of thermoplasmonics. The fundamental and applied aspects of thermoplasmonics have been extensively documented in the literature. ,, The importance of plasmonic heat lies in the huge amount of heat dissipated in a localized area. Our idea here was to use the plasmonic heat dissipated from Thy-AuNPs as the thermal energy source to evaporate the H 2 O from DMSO–H 2 O mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of the ligand composition (DDA and Thy) on the dynamic solvent-mediated self-assembly of AuNP was studied as well, which confirmed that a minimum amount of thymine thiol should be available on the surface of AuNPs to achieve a complete disassembly of NPs (Figure S13). In order to get a better insight into the controlled aggregation process, the interaction potentials were theoretically calculated using the extended Derjaguin–Landau–Verwey–Overbeek (EDLVO) model. , The interaction potential was considered as a sum of van der Waals force and steric force upon considering the soft-sphere model proposed by Korgel et al Therefore, the total interaction energy ( E total ) can be calculated as per eq E total = E vdW + E steric Here, E total is the total potential energy and E vdW and E steric are the van der Waals and the steric potential energy, respectively. The steric interaction is the main repulsive force that keeps the Thy-AuNP dispersed in the DMSO medium, eq , while the van der Waals force allows the AuNPs to attract each other during the self-assembly process, eq . E normals normalt normale normalr normali normalc = 100 R δ normalS normalA normalM 2 k normalB T π σ normalt normalh normali normalo normall 3 normale ( π D / δ S A M ) E vdW = prefix− A 12 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation